The man who lives with wolves - Ellis, Shaun. frey50; Junor, Penny (New York : Three Rivers Press, 2010)
The star of "Living with the Wolfman" shares the story of his decision to live among wolves, describing his efforts in the wilds of England's Norfolk and on Idaho's Nez Perce Indian Reservation, where he makes homes with two packs in captivity.
Includes index.
Keywords: Ellis, Shaun; Wolves -- Behavior; Human-animal relationships